2003
DOI: 10.1542/peds.112.5.1076
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Reminder and Recall Messages for Immunizations by Pediatricians and Public Health Clinics

Abstract: ABSTRACT. Objective. Strong scientific evidence and national recommendations support the use of reminder and recall messages to improve immunization coverage rates, yet reports have suggested that only a minority of pediatric practices use such messages. Our aims were to 1) determine the proportions of pediatric practices and public clinics that currently use practicebased reminder or recall messages and routinely undergo immunization assessment efforts, 2) evaluate barriers and supports to implementing these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 19 publications
1
69
0
Order By: Relevance
“…Further, the ease with which the SMS software can be accessed and applied in real-world settings significantly diminishes the required technical skill compared with other software-driven reminder systems, a factor which has been identified as a significant barrier to uptake of more technologically advanced reminder techniques. 14 In summary, this study indicates that SMS text messaging is a very efficacious technique to improve clinic attendance, access to services and revenue generation in the ambulatory care setting.…”
Section: Financial Benefitsmentioning
confidence: 73%
“…Further, the ease with which the SMS software can be accessed and applied in real-world settings significantly diminishes the required technical skill compared with other software-driven reminder systems, a factor which has been identified as a significant barrier to uptake of more technologically advanced reminder techniques. 14 In summary, this study indicates that SMS text messaging is a very efficacious technique to improve clinic attendance, access to services and revenue generation in the ambulatory care setting.…”
Section: Financial Benefitsmentioning
confidence: 73%
“…Although previous studies have shown that reminder-recall based interventions can improve immunization rates, few providers actually use these methods, especially in a population seeking care in the public sector. 10 Several investigators have examined the impact of various strategies of telephone and mail reminder-recall on childhood Figure 1. Up-to-date immunization rates by age for BIRTH PIP and CPS data.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Nevertheless, little evidence exists for the effectiveness of practice-based reminder/recall for adolescent immunizations, 15,16 although in one recent study in 4 practices researchers demonstrated increased immunization rates. 17 Moreover, few practices actually use reminder/recall for patients of any age [18][19][20] ; barriers include the added workload, costs, and complexities of conducting such a program. 21,22 Furthermore, some recent studies targeting low-income populations found little or no benefit to practice-based reminder/recall for young children because of difficulties in reaching families that often change addresses or telephone numbers.…”
Section: Introductionmentioning
confidence: 99%